Adherence to mediterranean diet and tendency to orthorexia nervosa in professional athletes - Martinovic, D.; Tokic, D.; Martinovic, L.; Vilovic, M.; Vrdoljak, J.; Kumric, M.; Bukic, J.; Ticinovic Kurir, T.; Tavra, M.; Bozic, J. (Nutrients, 2022)
Among many lifestyle components that professional athletes have to follow, nutrition is gradually growing to be one of the key factors for achieving and maintaining optimal sport performance. The Mediterranean diet (MD) is recognized as one of the healthiest dietary patterns worldwide; however, data regarding adherence to the MD among professional athletes are still scarce. Moreover, with the imposed need for a healthy diet among professional athletes, orthorexia nervosa (ON) could become a rising issue. This cross-sectional study included 150 professional athletes and 150 matched recreational athletes from Croatia. Four questionnaires were used for the assessment: general information, a test for the diagnosis of ON (ORTO-15), the International Physical Activity Questionnaire (IPAQ) and the Mediterranean Diet Serving Score (MDSS). Significantly more professional athletes were adherent to the MD (p < 0.001) and had a tendency to ON (p < 0.001). Moreover, there was a significant negative correlation between the ORTO-15 score and the total MET min/week score (r = -0.524, p < 0.001) and a significant positive correlation between the MDSS score and the total MET min/week score in the professional athlete group (r = 0.478, p < 0.001). All of these results imply that professional athletes are more concentrated on their dietary patterns than recreational athletes, and that due to this dedication, they possibly have a higher adherence to the MD but also possibly a higher risk for developing ON. However, the association between ON and the MD should be further addressed in the future.